ANALISIS PENGESAHAN FAKTOR KERENTANAN PETANI PASCA TSUNAMI DI ACEH - Adhiana Adhiana (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2017)
Limitations of access and loss of various life assets caused by tsunamis and conflicts inAceh faced by farmers have influenced their survival. The purpose of this research is toanalyze the model of determination factor of farmer life assets the post-tsunami in Aceh.This study was conducted in Aceh Province covering five areas: Aceh Barat, Aceh Besar,Pidie Jaya, Bireun and Aceh Utara. The total sample for this study was 280 farmers usingstratified random sampling method. This research uses primary data obtained by surveyusing quesioner and secondary data. Data analysis using qualitative and quantitativemethods with Structural Equation Modeling model is by measurement model. This model2 is used as the final model for the construct of the farmer's vulnerability factors as itdemonstrates a good model compatibility. It also indicates that all loading factor valueshave above 0.5 and all probability values are significant at a = 1%. It indicated that allindicators can explain the existing constructs.